1999
DOI: 10.1177/0261927x99018001002
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual and Phonetic Experiments on American English Dialect Identification

Abstract: The ability to discern the use of a nonstandard dialect is often enough information to also determine the speaker's ethnicity, and speakers may consequently suffer discrimination based on their speech. This article, detailing four experiments, shows that housing discrimination based solely on telephone conversations occurs, dialect identification is possible using the word hello, and phonetic correlates of dialect can be discovered. In one experiment, a series of telephone surveys was conducted; housing was re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
280
0
6

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 390 publications
(296 citation statements)
references
References 15 publications
10
280
0
6
Order By: Relevance
“…For example, on hearing a voice on the telephone, a landlord might deny accommodation to someone because the speaker is perceived to be of a particular race or from a particular place of origin. In fact research involving large numbers of untrained listeners hearing speech over the telephone has indicated that they can often guess the race or ethnicity of speakers after hearing them say only the word hello (Purnell, Idsardi, & Baugh, 1999). Unfortunately, the term linguistic profiling carries the unfortunate connotation of some sort of systematic, respectable, or even "scientific" evaluation of speakers, even though discrimination of this type is anything but precise or well informed.…”
Section: Accent Stereotypingmentioning
confidence: 99%
“…For example, on hearing a voice on the telephone, a landlord might deny accommodation to someone because the speaker is perceived to be of a particular race or from a particular place of origin. In fact research involving large numbers of untrained listeners hearing speech over the telephone has indicated that they can often guess the race or ethnicity of speakers after hearing them say only the word hello (Purnell, Idsardi, & Baugh, 1999). Unfortunately, the term linguistic profiling carries the unfortunate connotation of some sort of systematic, respectable, or even "scientific" evaluation of speakers, even though discrimination of this type is anything but precise or well informed.…”
Section: Accent Stereotypingmentioning
confidence: 99%
“…Perceived intelligence, for example, has been found to affect an individual's employability [28]. Landlords are found to discriminate against prospective tenants on the basis of the sound of their voice during telephone conversations [11]. Perceived task-ability, dominance, and sociability are found to show the strongest correlation with perceived influence in simulated juries [12].…”
Section: Discussionmentioning
confidence: 99%
“…For example, voice-based personality judgments are associated with mate selection [8], leader election [9,10], housing options [11], consumer choices, and jury decision [12]. Although researchers have demonstrated how vocal perception influences the communication process [13], it remains unclear whether such influences find resonances in a communicative setting like oral arguments at the Supreme Court of the United States (SCOTUS), where subtle biases have consequences for major policy outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Purnell (Purnell et al, 1999) showed that listeners could identify a dialect with only one word as information (closed choice, African American Vernacular English, Chicano English and Standard American English). Another study (Thomas, 2000) showed that a single segment in a certain context might be enough to distinguish between non-Hispanic whites from central Ohio and Mexican Americans from southern Texas.…”
Section: Identifying Languages and Accentsmentioning
confidence: 99%